Pore-scale study of the multiphase methane hydrate dissociation dynamics and mechanisms in the sediment - Yang, J; Xu, Q; Liu, Z; Shi, L (Elsevier BV, 2022)
Methane hydrate is a promising energy resource, but the hydrate development still faces technical difficulties due to the complicated multiple physicochemical and thermal processes during the multiphase hydrate dissociation in the sediment. In this study, a pore-scale numerical model based on the lattice Boltzmann method was proposed to simulate methane hydrate dissociation considering multiphase flow, heat and species transport, heterogeneous reaction and hydrate structure evolution. The single-phase hydrate dissociation was firstly simulated to identify the convection and diffusion transport-limited regimes according to the Péclet number. Effects of the connate water saturation and the Péclet number on the multiphase hydrate dissociation were then investigated to understand the varying dissociation dynamics and dissociation mechanisms. The competitive mass-transfer-limitation and heat-transfer-limitation were quantified to elucidate the interplay between multiphase mass transport and heat transport on the hydrate recovery efficiency. The regime diagram of the methane hydrate dissociation was mapped to exhibit five dissociation regimes according to the connate water saturation and the Péclet number. Empirical correction of the permeability and the specific surface area was obtained to improve the REV (Representative Element Volume)-scaled modeling accuracy of the volume-averaged transport and geometric properties with three typical dissociation patterns. The insights from the pore-scale multiphase dissociation studies can enlighten the accurate REV-scaled simulation with the addressed non-negligible physics.